Following the Tracks of the First South Americans - Bayón, María Cristina; Manera, Teresa; Politis, Gustavo; Aramayo, Silvia Azucena (Springer, 2011)
In this article, a summary of the geologic, paleontological, and human history of an area of the Atlantic coast in the Pampean plain, Argentina is discussed. This area presents very interesting characteristics. On the one hand, the area includes the Monte Hermoso cliffs studied by Charles Darwin in 1832, which compose the set of localities related to the development of the theory of evolution. On the other hand, in the referred area, an extraordinary amount of human and Pleistocene mammal footprints are registered. Also in that section, four diachronic stages have been registered which depict the evolutionary scenario during the last five million years. Four paleontological and archeological sites are described, showing the palaeoenvironmental changes that occurred there regarding fauna associations and human settlement. The first scenario is found at Monte Hermoso cliff, whose sediments contain fossil remains of the autochthonous South American fauna. The second scenario shows a remarkable change in the drainage system where the fauna is composed of immigrated taxa due to the Great American Biotic Interchange. Both last scenarios show human presence; the third one shows faint evidences (one human trackway and two isolated footprints), and in the last one the hunter–gatherers are fully represented as a well-established population on the Pampean coast during the Early Holocene, registered at La Olla and Monte Hermoso I sites. In this way, the sites summarized in this work allow the reconstruction of four remarkable evolutionary scenarios in South America, as regards landscapes, fauna associations, and human population.